Phlebotomine sand fly survey in the Republic of Moldova: species composition, distribution and host preferences - Șuleșco, Tatiana; Erisoz Kasap, Ozge; Halada, Petr; Oğuz, Gizem; Rusnac, Dimian; Gresova, Marketa; Alten, Bulent; Volf, Petr; Dvorak, Vit (Parasites & vectors, 2021)
BACKGROUND: Phlebotomine sand flies (Diptera: Psychodiae) in the Republic of Moldova have been understudied for decades. Our study provides a first update on their occurrence, species composition and bloodmeal sources after 50 years. METHODS: During 5 seasons (2013-2017), 58 localities from 20 regions were surveyed for presence of sand flies using CDC light traps and manual aspirators. Species identification was done by a combination of morphological and molecular approaches (DNA barcoding, MALDI-TOF MS protein profiling). In engorged females, host blood was identified by three molecular techniques (RFLP, cytb sequencing and MALDI-TOF peptide mass mapping). Population structure of most abundant species was studied by cox1 haplotyping; phylogenetic analyses of ITS2 and cox1 genetic markers were used to resolve relationships of other detected species. RESULTS: In total, 793 sand flies were collected at 30 (51.7%) localities from 12 regions of Moldova. Three species were identified by an integrative morphological and molecular approach: Phlebotomus papatasi, P. perfiliewi and Phlebotomus sp. (Adlerius), the first being the most abundant and widespread, markedly anthropophilic based on bloodmeal analyses, occurring also indoors and showing low population structure with only five haplotypes of cox1 detected. Distinct morphological and molecular characters of Phlebotomus sp. (Adlerius) specimens suggest the presence of a yet undescribed species. CONCLUSIONS: Our study revealed the presence of stable sand fly populations of three species in Moldova that represent a biting nuisance as well as a potential threat of pathogen transmission and shall be further studied.
Keywords: Psychodidae; haplotypy; Male; MALDI-TOF MS protein profiling; fylogeneze; Bloodmeal analysis; Phylogeny; Leishmaniasis; Haplotypes; mužské pohlaví; hmyz - vektory; hostitelská specificita; Animals; lidé; ženské pohlaví; Moldova; Humans; zvířata; Moldavsko; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Insect Vectors; leishmanióza; Female; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Haplotype network; Host Specificity; Phlebotomus